2005
DOI: 10.1258/0049475053001958
|View full text |Cite
|
Sign up to set email alerts
|

Winter peak of respiratory syncytial virus in Islamabad

Abstract: A study was carried out on 391 cases of bronchiolitis and pneumonia from different paediatric units in Rawalpindi/Islamabad, Pakistan. A clear winter spike of respiratory syncytial virus (RSV) was noted. It was found that there was a substantial increase of 30-50% in the positivity of RSV from December to February.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 3 publications
1
9
0
Order By: Relevance
“…Our findings are also consistent with a previous study conducted in a large public sector tertiary care hospital of Karachi, Pakistan . On the other hand, a study from Islamabad and Rawalpindi, Pakistan, showed that RSV was frequently detected from December through February . This is likely due to climatic differences between different cities, with Islamabad and Rawalpindi having temperate climate while Karachi having milder, coastal climate.…”
Section: Discussionsupporting
confidence: 91%
“…Our findings are also consistent with a previous study conducted in a large public sector tertiary care hospital of Karachi, Pakistan . On the other hand, a study from Islamabad and Rawalpindi, Pakistan, showed that RSV was frequently detected from December through February . This is likely due to climatic differences between different cities, with Islamabad and Rawalpindi having temperate climate while Karachi having milder, coastal climate.…”
Section: Discussionsupporting
confidence: 91%
“…Children aged between 2 months and 3 years were enrolled for study. Results pointed out the significant increase of about 50% in activity of RSV in winter . Another study conducted in Agha Khan University Hospital, Karachi identified 27 positive cases for influenza A(H1N1)pdm09.…”
Section: Discussionmentioning
confidence: 97%
“…Nasopharyngeal aspirates were collected from different pediatric units of Rawalpindi and Islamabad for analysis purpose. Eighty samples showed positivity for RSV with a clear peak activity in winter season . Another study conducted in Karachi from August 2009 to September 2011 reported 13 out of the 27 cases diagnosed with pneumonia which were positive for influenza A(H1N1)pdm09 .…”
Section: Discussionmentioning
confidence: 99%
“…The study from United Arab Emirates provided inconclusive data defining RSV seasonality as it was conducted for only 3 months (September to November) [54]. Seven out of eleven studies from the Eastern Mediterranean were spanned only for short periods less than 12 months, and probably were insufficient to obtain information on seasonality [42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57] (Table 3). Iran, Tehran [47] Nov 97 -Mar 98 Winter…”
Section: Eastern Mediterraneanmentioning
confidence: 99%